Validity test of digital learning content in social science education for junior high schools in Singaraja city - Utami, Anak Agung Istri Dewi Adhi; Suastika, I Nengah; Mudana, I Wayan; Sriartha, I Putu; Sujana, I Putu Windu Mertha; Budiarta, I Wayan; Sidaryanti, Ni Nyoman Asri; G. Vann, Michael (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
This research aims to analyse the needs for developing digital learning media in Social Sciences learning in junior high schools in Singaraja City. This study used qualitative research methods. The process of developing learning media must be carried out by testing construct validity and empirical validity. Material experts, media experts and language experts will carry out validity testing. The results of the analysis of social science education material experts assessed the validity score of the material to be 93, or the criteria "Very Valid". Likewise, the graphic design value is 90 or the "Very Valid" criteria. Meanwhile, the level of grammatical validity is 88 or the criteria "Very Valid". Based on the results obtained through expert testing in the media, material and language aspects, it can be concluded that the developed digital learning media is declared very valid, so it is suitable for use in the social science education learning process. The practicality test of digital learning media was assessed by two social science education groups and 24 students participating in social science education learning. The average score given by social science education teachers was 87.69, or Very Good criteria. Meanwhile, the practicality test assessment is based on assessing students taking social science education subjects with a score of = 79.48 or good criteria. These results show that the digital such as media developed can be used sustainably. This is because teachers and students assess that this digital learning media aligns with the needs of teachers and students.